Isolated zero-voltage switching two-inductor boost converter with two coupled input inductors and one magnetic core - Wolfs, Peter; Li, Q. (Engineers Australia, 2009)
The isolated two-inductor boost converter with an auxiliary transformer has been previously proposed for applications where the low voltage inputs need to be transformed to high voltage outputs. In order to utilise the leakage inductance of the isolation transformer, the zero-voltage switching (ZVS) topology can be employed. However, a large component count exists in the resonant converter and this contributes to cost and size. In this paper, a new ZVS isolated two-inductor boost converter with two coupled input inductors and an integrated magnetic structure is proposed. In the proposed topology, the seven copper windings and the five magnetic cores required by the auxiliary transformer, the two input inductors, the resonant inductor and the isolation transformer in the discrete magnetic arrangement are integrated into one magnetic core with four copper windings. This paper establishes the inherent relationship between the integrated and the discrete magnetic implementations of the isolated ZVS two-inductor boost converter with two coupled input inductors through the switching state and magnetic circuit analyses. This significantly simplifies the analysis of the new converter with the magnetic integration by modelling the converter with its discrete magnetic equivalent. Finally, both the theoretical and the experimental waveforms of a 1 MHz 100 W converter are provided and they agree well with each other.